A Fresh Look at Anxiety Disorders - Durbano, Federico (IntechOpen, 2015)
This book, the ideal following of the previous New Insights into Anxiety Disorders, collects papers of a number of clinical psychiatrists all over the world, giving their contribution to the comprehension and clinical management of anxiety disorders. Following the previously edited book on anxiety, this new one will focus on some specific clinical issues such as PTSD, psychosomatics, and complementary approaches to anxiety management themes which were not discussed in the previous book.